TREATMENT OF DISORDERS OF THE MENSTRUAL CYCLE IN WOMEN WITH METABOLIC SYNDROME - Мамедгасанов Р. М.; Аббасова Л. К.; Мешадиева С. Е. (World of Medicine and Biology, 2015)
Internal diseases Department of Azerbaijan Medical University, Baku The article provides information about the study and treatment of disorders of the menstrual cycle in women with metabolic syndrome. In a study conducted from 2011 to 2013, included the results of a survey of 50 patients with metabolic syndrome before and after treatment, complaining of menstrual irregularities. The study showed that menstrual irregularities in women with metabolic syndrome are mainly related to the presence of polycystic ovary syndrome. Menstrual irregularities were mainly in the type of oligomenorrhea and amenorrhea. Treatment of disorders of the menstrual cycle in women with metabolic syndrome drug Galvusmet 50/1000 mg gave positive results. The results showed that during the first 6 months of treatment in women with 1 and 2 degree obesity BMI is normalized. Fasting insulin level in these groups has fallen to normal, menstrual cycle is normal (26 – 31 days). Women with a third degree of obesity, the weight decreased to the first degree of obesity, the menstrual cycle was restored (34 – 40 days). The results of the treatment of women with menstrual disorders and metabolic syndrome (polycystic ovaries with insulin resistance) showed that the drug Galvusmet 50/1000 mg is effective in the treatment of this disease.